2021
DOI: 10.1088/1361-665x/abd90f
|View full text |Cite
|
Sign up to set email alerts
|

Active feedforward control of flexural waves in an Acoustic Black Hole terminated beam

Abstract: Acoustic Black Holes (ABHs) are structural features that are typically realised by introducing a tapering thickness profile into a structure that results in local regions of wave-speed reduction and a corresponding enhancement in the structural damping. In the ideal theoretical case, where the ABH tapers to zero thickness, the wave-speed reaches zero and the wave entering the ABH can be perfectly absorbed. In practical realisations, however, the thickness of the ABH taper and thus the wave-speed remain finite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Existing researches on ABH are grooming in the past few decades, including many aspects such as theoretical analyses [3][4][5][6][7][8], experimental researches [9][10][11][12], structural design [13][14][15][16][17], optimization [18][19][20] and some burgeoning engineering applications such as vibration and noise reduction and energy recovery [21][22][23][24][25]. The most recent evaluations of the state-of-the-art in ABH research as well as some prospective applications were provided by Pelat et al [26] and Zhao et al [27] However, in the majority of the researches mentioned above, ABH is embedded into a structure via thinned thickness..…”
Section: Introductionmentioning
confidence: 99%
“…Existing researches on ABH are grooming in the past few decades, including many aspects such as theoretical analyses [3][4][5][6][7][8], experimental researches [9][10][11][12], structural design [13][14][15][16][17], optimization [18][19][20] and some burgeoning engineering applications such as vibration and noise reduction and energy recovery [21][22][23][24][25]. The most recent evaluations of the state-of-the-art in ABH research as well as some prospective applications were provided by Pelat et al [26] and Zhao et al [27] However, in the majority of the researches mentioned above, ABH is embedded into a structure via thinned thickness..…”
Section: Introductionmentioning
confidence: 99%
“…An active solution to this problem has been presented for an active ABH (AABH) beam termination in [17], where it has been shown that a feedforward wave-based control strategy can be applied to control the reflection coefficient of the AABH. For a plate with embedded ABHs, the reflection coefficient with respect to structural waves is less obviously defined and, therefore, previous research on ABHs embedded in plates has focused on different structural metrics, such as surface mobility [1,9] and mean-squared acceleration/velocity [5,6,18].…”
Section: Introductionmentioning
confidence: 99%
“…To increase the low frequency performance of an ABH and also increase its potential adaptability, an active solution has been proposed in which an active vibration control system is integrated into an ABH beam termination [18]. This active ABH (AABH) utilises a feedforward wave-based control strategy, which can control the reflection coefficient in the beam using a piezoelectric patch actuator attached to the ABH taper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Acoustic Black Hole (ABH), which is currently the subject of extensive research [1,2,3,4], is a response to this challenge. Its usual implementation in a one dimensional (1D) system consists in locally thinning the thickness of a beam according to a power-law profile and coating it with a visco-elastic layer [5,6].…”
Section: Introductionmentioning
confidence: 99%